2019
DOI: 10.1891/1933-3196.13.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial: EMDR Early Intervention With and Without Eye Movements for Learned Helplessness State

Abstract: Learned helplessness (LH) is considered a psychological trait, which occurs after repeated exposure to aversive and uncontrollable situations (Seligman, 1975). Such an exposure is found to lead motivational, cognitive, and emotional deficits. LH has also been linked to different psychological disorders such as depression, anxiety, posttraumatic stress disorder (PTSD), and trauma-related depression. Eye movement desensitization and reprocessing (EMDR) therapy has been accepted as an efficacious treatment for PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, memory becomes less distressing, which, based on several studies (e.g., van den Hout et al, 2012), is then reconsolidated in a less disturbing form (Shapiro, 2017). Recent studies have shown the importance of the EM component in reducing the vividness and emotionality of unpleasant memories (Onderdonk & van den Hout, 2016; van Veen et al, 2016) and also the necessity of the EM component in reversing the emotional deficits induced by an acute stress reaction (Egĕci & Özgün, 2019). Moreover, Landin-Romero et al (2018) studied the suggested mechanisms of action in EMDR treatment in a systematic review and provided a reasonable empirical support for the physiological changes following successful EMDR treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, memory becomes less distressing, which, based on several studies (e.g., van den Hout et al, 2012), is then reconsolidated in a less disturbing form (Shapiro, 2017). Recent studies have shown the importance of the EM component in reducing the vividness and emotionality of unpleasant memories (Onderdonk & van den Hout, 2016; van Veen et al, 2016) and also the necessity of the EM component in reversing the emotional deficits induced by an acute stress reaction (Egĕci & Özgün, 2019). Moreover, Landin-Romero et al (2018) studied the suggested mechanisms of action in EMDR treatment in a systematic review and provided a reasonable empirical support for the physiological changes following successful EMDR treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Learned helplessness refers to a pattern of thoughts and behavior instigated by repeated or intense, uncontrollable adverse events, that increases the likelihood of psychopathology, especially depression [ 138 ]. This study aims to build on earlier analyses investigating the impact of trauma-focused treatments on levels of learned helplessness [ 139 ]. Further, the role of learned helplessness as a possible mediator of change, especially for participants who have a comorbid depression diagnosis, will be investigated.…”
Section: Methodsmentioning
confidence: 99%